Network of Mediators for Vascular Inflammation and Leakage Is Dysbalanced during Cytoreductive Surgery for Late-Stage Ovarian Cancer. (17th July 2019) - Klaschik, Sven; Gehlen, Jennifer; Neumann, Claudia; Keyver-Paik, Mignon-Denise; Soehle, Martin; Frede, Stilla; Velten, Markus; Hoeft, Andreas; Hilbert, Tobias
Abstract : Background . Cytoreductive surgery (CS) in late-stage ovarian cancer patients is often challenging due to extensive volume shifts, and high fluid intake may provoke postoperative complications. Expression of vasoactive mediators is altered in cancer patients, which may affect systemic vascular function. We sought to assess how serum levels of vasoactive markers and mediators change during CS in ovarian cancer. Methods . Following IRB approval and informed consent, pre- and postoperative serum samples were analyzed in 26 late-stage ovarian cancer patients using multiplex protein arrays and ELISA. Results . The proinflammatory cytokines and chemokines IL-6, IL-8, and CCL2 were significantly elevated after 24 hrs compared to the baseline values, with IL-6 and IL-8 being most prominently increased. While ANGPT1 remained unchanged after surgery, its competitive antagonist ANGPT2 was significantly increased. In contrast, serum levels of the ANGPT receptor TIE2 were decreased to 0.6 of the baseline values. While VEGF-D, E-selectin, P-selectin, ICAM-1, and PECAM-1 remained unchanged, serum activity of both thrombomodulin and syndecan-1 was significantly increased following surgery. Conclusion . We identified a regulatory network of acute-phase reaction during CS in late-stage ovarian cancer. This suggests that IL-6 exerts positive regulation of other proinflammatory mediators and, by upregulating ANGPT2 and suppressing ANGPT1, induces a serum profile that promotes vascular leakage. This may contribute to the observed hemodynamic alterations during CS procedures.